Taxonomy and phylogeny of Sanguinoderma rugosum complex with descriptions of a new species and a new combination - Sun, Yi-Fei; Fang, Yu-Xuan; Cui, Bao-Kai (Frontiers in Microbiology, 2022)
Sanguinoderma is distributed in tropical and subtropical areas as a member of Amauroderma s. lat., and the economic values of Sanguinoderma led to high attention in the taxonomic studies. Previously, 16 species have been developed into Sanguinoderma. In this study, the taxonomic system of Sanguinoderma was reconducted based on morphological and multi-gene phylogenetic analyses, especially making a distinction for Sanguinoderma rugosum complex. Morphological analysis was based on the notes of macro- and micro morphological observations. Multi-gene phylogenetic analyses were used maximum likelihood (ML) and Bayesian inference (BI) analyses inferred from combined dataset of ITS, nLSU, rpb2, tef1, mtSSU, and nSSU. Combined with morphological characters and phylogenetic evidence, the results demonstrated that S. rugosum complex consists of five taxa, in which Sanguinoderma leucomarginatum was described as a new species, and it is characterized by the orbicular pilei with white to buff margin when fresh and clavate apical cells of pileipellis with septa. In addition, Amauroderma preussii was transferred to Sanguinoderma as a new combination due to its blood-red color-changed pore surface; it is characterized by the funnel-shaped, greyish brown, and glabrous pilei with strongly incurved margin. Detailed descriptions and photographs of the two species were provided. With the extension of this study, 18 species were accepted in Sanguinoderma, and 12 species among them were distributed in China. A key to accepted species of Sanguinoderma was also provided.